Penumbuhan Spiritualitas Santri Melalui Dzikir Khulasah Madad Nabawi. - Raudhatul Umi; Saiful Bahri (al-Iltizam: Jurnal Pendidikan Agama Islam, 2026)
This study aims to describe and analyse the process of fostering students’ spirituality through the practice of Dzikir Khulasah Madad Nabawi at Al-Husainy Islamic Boarding School. The research employed a qualitative approach with a case study design. The participants consisted of the pesantren leader, spiritual mentors, and students who actively participated in the dzikir activities. Data were collected through observation, semi-structured interviews, and documentation, and were analysed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through methodological triangulation. The findings reveal that Dzikir Khulasah Madad Nabawi serves as a means of fostering students’ spirituality through a continuous habituation process. The resulting spirituality is characterised by a stronger sense of closeness to Allah, inner peace, tawakkul (trust and reliance on Allah), self-control, discipline in worship, and the development of good moral character. The habituation of dzikir not only generates spiritual awareness at an inner level but also influences students’ daily behaviour, including increased politeness, greater respect for teachers and parents, and the ability to maintain harmonious social relationships. Therefore, Dzikir Khulasah Madad Nabawi functions not merely as a ritual practice but also as an instrument of spiritual education that contributes to the holistic development of students’ personalities